(untitled) (Nordic Journal of African Studies, 2011)
The period that runs from 1964 to 1980 was special to Malawi for mainly three reasons: (1) the apparent unique approach to development as compared to other African countries; (2) its unprecedented economic growth; (3) arguably the only period whereby Dr Banda, Malawi’s first president, had almost total control of the country’s economic and development policies. Through a comparative literature review of economic history sources, the paper points out that these conditions create a plausible reason for a deeper critical analysis of the economic and development policies that were being pursued. Although it can be concluded that economic growth and development is a product of mainly external socio-economic/political factors, the paper argues that Dr Banda’s pragmatic policy choices and determination played a critical role to the recorded progress in the said period. These policy choices may distinctively be referred to as ‘Pragmatic Unilateral Capitalism’.